2005
DOI: 10.1149/1.2013210
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SiO Anodes for Lithium-Ion Batteries

Abstract: The chemical structure of SiO ͑silicon monoxide͒ anodes has been analyzed using X-ray photoelectron spectroscopy ͑XPS͒. Vapor deposition was used to form SiO anodes on Cu film. XPS analysis was performed on anodes at each of three stages: after deposition, after initial charge, and after discharge. The results of this analysis were then evaluated in terms of the anode's respective electrochemical characteristics. It has been found that some Si remains oxidized in the full charge state and that lithium silicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
265
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(284 citation statements)
references
References 11 publications
9
265
0
3
Order By: Relevance
“…25,33,34,36 Additionally, peaks of Li x Si at 98.4 eV and 98.9 eV are clearly identifiable. 25,33,34,36 The presence of Li-Si bonds is not attributed to a Li-Si alloying reaction because it happens at potentials above 0.5 V. 17 However, the intrinsic SiO 2 layer on Si(100) reacts with Li + , resulting in a partial conversion of the surface oxide to Li 2 O and lithium silicates Li 2 Si 2 O 5 at 0.5 V. [37][38][39][40] The presence of SiOF in the samples from FEC-and VC-containing electrolytes as indicated by the signals at 105.1 and 105.6 eV, is fully consistent with the corresponding F 1s XPS spectra ( Figure 6). 33,34,36 The Si-O peaks from SiO 2 at 103.6 and 104.2 eV 19,33,34,36 and a small amount of lithium silicates at 101.0 and 101.6 eV 33,34,36 can also be observed.…”
Section: Resultsmentioning
confidence: 99%
“…25,33,34,36 Additionally, peaks of Li x Si at 98.4 eV and 98.9 eV are clearly identifiable. 25,33,34,36 The presence of Li-Si bonds is not attributed to a Li-Si alloying reaction because it happens at potentials above 0.5 V. 17 However, the intrinsic SiO 2 layer on Si(100) reacts with Li + , resulting in a partial conversion of the surface oxide to Li 2 O and lithium silicates Li 2 Si 2 O 5 at 0.5 V. [37][38][39][40] The presence of SiOF in the samples from FEC-and VC-containing electrolytes as indicated by the signals at 105.1 and 105.6 eV, is fully consistent with the corresponding F 1s XPS spectra ( Figure 6). 33,34,36 The Si-O peaks from SiO 2 at 103.6 and 104.2 eV 19,33,34,36 and a small amount of lithium silicates at 101.0 and 101.6 eV 33,34,36 can also be observed.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] SiO shows a small volume change because it contains a relatively small amount of Si element that is active for the alloying reaction. The discharge capacity of SiO electrodes was reported to be over 600 mAh g −1 in several papers, [9][10][11][12] which is much higher than that of a graphite electrode ͑372 mAh g −1 ͒. To commercialize the SiO electrode, we need to consider the rate performance in addition to the energy density.…”
mentioning
confidence: 99%
“…The nano-silicon then reacts with Li and forms Li-Si alloy (Lee & Lee, 2004). Contrary to this explanation (Miyachi et al, 2006) showed through O 1s spectra analysis that during the first lithiation process a direct absorption of Li by SiO takes place giving rise to the formation of Li 4 SiO 4 and Li 2 O. Among the composites prepared, the 24 h ball-milled sample exhibits higher reversible capacity.…”
Section: Charge/discharge Characteristicsmentioning
confidence: 91%